PANCASILA SEBAGAI IDENTITAS DAN NILAI LUHUR BANGSA: ANALISIS TENTANG PERAN PANCASILA SEBAGAI MODAL SOSIAL BERBANGSA DAN BERNEGARA - Susanto Susanto (JIIP: Jurnal Ilmiah Ilmu Pemerintahan, 2016)
Pancasila is the highest value of ideology compared to other ideologies. Even, Pancasila is the source of all sources of law. Crisis of identity that struck Indonesia nowadays, is one manifestation of the weakening values of Pancasila ideology which caused by a lack of trust in the implementation of Pancasila as social capital state and nation. The capitalism and fundamentalism appear as a manifestation of the faint of national identity. It showed by some cases, such as the emergence of separatist movements and corruption. Riots or small-scale conflicts or individual can develop into large-scale conflict or SARA (Suku, Agama, Ras, dan Antar Golongan) which result damage of public facilities and infrastructure. Since the Orde Lama, Orde Baru, until the Reformation, the Pancasila ideology has a very different role. The Era of Orde Lama is the beginning of the birth of Pancasila and in the Orde Baru, Pancasila was used as a tool to maintain power, and finally the Reformation where the appreciation of Pancasila values increasingly faded because of distrust and so it raises the capitalism and fundamentalism. A suggestion to minimize crisis of national identity is by awareness of meaning and values contained in the Pancasila ideology. We should return to the real values of the Pancasila.